Functionally modified chitotriosidase catalytic domain for chitin detection based on split-luciferase complementation. (15th April 2022) - Yamanaka, Daisuke; Suzuki, Kento; Kimura, Masahiro; Oyama, Fumitaka; Adachi, Yoshiyuki
Abstract: In this study, we applied a luciferase-fragment complementation assay for chitin detection. When luciferase-fragment fused chitin-binding proteins were mixed with chitin, the reconstituted luciferase became active. The recombinant chitin-binding domain (CBD) and a functionally modified catalytic domain (CatD) of human chitotriosidase were employed for this method. We designed the CatD mutant as a chitin-binding protein with diminished chitinolytic activity. The non-wash assay using the CatD mutant had higher sensitivity than CBD for chitin detection and proved to be a structure-specific biosensor for chitin, including crude biomolecules (from fungi, mites, and cockroaches). The CatD mutant recognized a chitin-tetramer as the minimal binding unit and bound chitin at K D 99 nM. Furthermore, a sandwich ELISA using modified CatD showed a low limit of quantification for soluble chitin (13.6 pg/mL). Altogether, our work shows a reliable method for chitin detection using the potential capabilities of CatD. Graphical abstract: Unlabelled Image